Strategies for Implementing the Concept of Green Economics in Promoting Sustainable Development: An Empirical Study in Purwakarta District - Fidya Nugroho, Alviano; Azidan, Ikhsan; Fandi Permana, Adi (International Journal of Law Social Sciences and Management, 2024)
This study provides recommendations for local government and stakeholders on optimal strategies in implementing green economics to achieve sustainable development in Purwakarta District, as well as evaluating the effectiveness of these strategies and identifying key challenges. This study used a qualitative approach with a case study method to explore in depth the strategies for implementing green economics concepts in promoting sustainable development in Purwakarta District. The main data was collected through in-depth interviews with Purwakarta District agencies related to the implementation of green economics and sustainable development. SWOT analysis was used to identify strengths, weaknesses, opportunities, and threats in the application of the green economics concept in Purwakarta District. Data obtained from interviews and group discussions were analyzed using NVivo 12 Plus software. This study found that the strategies for implementing the concept of green economics in encouraging sustainable development in Purwakarta Regency include integrating environmental policies in development plans, promoting environmental education and awareness, partnering with the private sector and the community, and developing renewable energy. There are also five strategies for implementing the concept of green economics in encouraging sustainable development in Purwakarta Regency, including 1) forming a special team, 2) socialization, 3) collaboration, 4) making people aware, 5) policies supported by technology, 6) handling waste, 7) regulation, 8) utilizing potential. Challenges faced include limited resources, social resistance, poor inter-agency coordination, and inadequate regulations. Recommendations to address these issues are capacity building, continuous education and campaigns, improved coordination, and policy revisions. The findings provide valuable insights for policymakers in strategizing sustainable development in the region. This research makes a significant contribution to the local environmental policy literature and offers practical guidance for policy makers in Purwakarta. The results of this study enhance community and private sector participation in green initiatives and provide insights that can be adapted for sustainable development in other regions.